1998
DOI: 10.1182/blood.v92.10.3616.422k19_3616_3623
|View full text |Cite
|
Sign up to set email alerts
|

Two New Pseudopod Morphologies Displayed by the Human Hematopoietic KG1a Progenitor Cell Line and by Primary Human CD34+Cells

Abstract: A primitive human hematopoietic myeloid progenitor cell line, KG1a, characterized by high expression of the CD34 surface antigen has been observed to extend long, thin pseudopodia. Once extended, these pseudopods may take on one of two newly described morphologies, tenupodia or magnupodia. Tenupodia are very thin and form in linear segments. They adhere to the substrate, can bifurcate multiple times, and often appear to connect the membranes of cells more than 300 μm apart. Magnupodia are much thicker and have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 33 publications
1
24
2
Order By: Relevance
“…To investigate a potential role and association of CD34 with cell adhesion/membrane activation, CB and BM HPSC were allowed to adhere to microscope slides at room temperature to permit active membrane interaction with the slide or adjacent cells. Magnupodia were observed on CB and BM samples by DIC imaging, reported by Francis et al , 1998), and defined as bulb‐like membrane projection, capable of rapid dynamic behaviour (Francis et al , 1998). Fluorescent membrane dye (PKH26) has been used previously with CD34 + CB cells, shown to extend pseudopodia, forming adhesion interactions with substrate (Francis et al , 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate a potential role and association of CD34 with cell adhesion/membrane activation, CB and BM HPSC were allowed to adhere to microscope slides at room temperature to permit active membrane interaction with the slide or adjacent cells. Magnupodia were observed on CB and BM samples by DIC imaging, reported by Francis et al , 1998), and defined as bulb‐like membrane projection, capable of rapid dynamic behaviour (Francis et al , 1998). Fluorescent membrane dye (PKH26) has been used previously with CD34 + CB cells, shown to extend pseudopodia, forming adhesion interactions with substrate (Francis et al , 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Magnupodia were observed on CB and BM samples by DIC imaging, reported by Francis et al , 1998), and defined as bulb‐like membrane projection, capable of rapid dynamic behaviour (Francis et al , 1998). Fluorescent membrane dye (PKH26) has been used previously with CD34 + CB cells, shown to extend pseudopodia, forming adhesion interactions with substrate (Francis et al , 1998). This has been further defined by electron microscopy, when CD34 was found to localize primarily to small membrane protrusions, demonstrating rapid membrane activity (McGuckin et al , 2000; Hayward‐Costa et al , 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have coined the term proteopodia' to describe these extensions, after the ancient Greek deity Proteus, the Old Man of the Sea, who could foretell the future and change shape at will. Francis et al (1998) have reported pseudopodia on a human haematopoietic stem cell-enriched population and on haematopoietic cell lines. That study did not observe highly purified stem cells, however, the pseudopodia described therein bear some similarities to the proteopodia we report here.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, despite the molecular characterization of HSCs, their three-dimensional surface morphology has not been closely studied. The morphology of HSCs is traditionally considered to vary between that of a transitional lymphocyte or a blast cell, however, a recent report demonstrated two different types of pseudopodia on a stem cell-enriched population and a haematopoietic progenitor cell line (Francis et al, 1998), indicating that the surface morphology of HSCs is more complex than had been thought.…”
mentioning
confidence: 98%